Persepsi dan Keputusan Wisatawan dalam Membeli Produk Berlabel Green Product di Desa Wisata Panglipuran, Bali - Komang Candra Dewi, Luh; Widagdo, Suwignyo (RELASI : JURNAL EKONOMI, 2024)
The purpose of this study is to analyze the influence of tourist perceptions and decisions on the purchase of green products labeled products in Panglipuran Bali Tourism Village and to determine the influence of tourist decisions on and purchases of green products labeled products in Penglipuran Bali Tourism Village, in this study using quantitative research using data analysis from software from smartPLS 4.0, then in testing conducted by researchers among others as follows, the number of latent variables in this study is 4 variables, namely Perception (PR), Tourist Decision (TD) is an endogenous variable, while exogenous variables are Purchase (PMB) and Green Products. (GP). Furthermore, the results of respondents' answers will be processed and analyzed with smartPLS-SEM 4.0 software analysis techniques. The formulas are tested for convergent and discriminant validity, reliability, construct multicollinearity, R Square Test, F-Square Model Conformity Test (F2) and Path Coefficient Test. Based on the results of the hypothesis test, it shows that the hypothesis test in this study was carried out by looking at the t-statistical value and p-value. A research hypothesis is considered acceptable if the t-statistic value is greater than 1.65 and the p value < 0.05. Furthermore, it is known to test the hypothesis that this study shows the results for the results of H1 analysis, namely the perception of a significant effect on the purchase of green product-based products in Panglipuran Tourism Village Bali, by looking at the statistical value of T of 2.3150, then at the P value of 0.0113 smaller than 0.05, in other words that H1 is accepted. Then on H2 about the influence of tourist decisions that have a significant effect on the purchase of products labeled green products in Panglipuran Tourism Village Bali can be seen with a statistical value of T of 2.4835, then for the P veleus value of 0.1201, with the results of this hypothesis test that for H2 is acceptable.